Membangun Sumber Daya Manusia yang Unggul dengan Pengembangan Pola Pikir Melalui Pelatihan Budi Daya Sayur Hidroponik - Asib Dwi Kuryanto; Eko Restiyono; Dina Hariati; Cindy Clarissa; Ulfa Nur Azizah (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2026)
Community service is a strategic effort to enhance the capacity and empowerment of village communities. This activity was conducted in Gedog Wetan Village, Turen District, Malang Regency, focusing on training in vegetable hydroponic cultivation and the development of a growth mindset. The primary goal of the activity was to increase the knowledge, skills, and confidence of community members in adopting modern agricultural technology and to foster an innovative mindset. The method employed was an educational- participatory approach, involving direct practice and ongoing mentoring. The results indicated an increase in participants' interest and understanding of hydroponics and growth mindset, although evaluation and product marketing still require strengthening. This activity provides a foundation for sustainable agriculture development and economic empowerment within the community